2017
DOI: 10.1093/arclin/acx009
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Validity Testing Recommendations in Neuropsychological Assessment: A Survey of INS and NAN Members

Abstract: Results highlight the need for continued training on the importance of validity testing practices across different countries and all assessment settings, and identify groups of neuropsychologists to whom training could be targeted to maximize effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
0
4
0
16
Order By: Relevance
“…In fact, a survey conducted by Martin et al (2015) found that neuropsychologists tend to administer an average of four to six PVTs. Similarly, Hirst et al (2017) recently reported that Veterans Affairs health care providers typically administer five to eight PVTs. Ultimately, the overall clinical presentation is generally considered not credible if multiple independent PVTs (typically two or more) do not look credible (Larrabee et al, 2019; Sherman et al, 2020).…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…In fact, a survey conducted by Martin et al (2015) found that neuropsychologists tend to administer an average of four to six PVTs. Similarly, Hirst et al (2017) recently reported that Veterans Affairs health care providers typically administer five to eight PVTs. Ultimately, the overall clinical presentation is generally considered not credible if multiple independent PVTs (typically two or more) do not look credible (Larrabee et al, 2019; Sherman et al, 2020).…”
Section: The Current Meta-analysismentioning
confidence: 99%
“…As of 2015, surveys indicate that neuropsychologists, on average, administer four to six PVTs in total (i.e., three to four embedded PVTs and one to two stand-alone PVTs in each evaluation; Martin, Schroeder, & Odland, 2015 ). Within Veterans Affairs health settings, neuropsychologists report using five to eight PVTs ( Hirst et al, 2017 ), and when performance validity is assessed, 89% of neuropsychologists employ at least two PVTs ( Young, Roper, & Arentsen, 2016 ). Surveys of experts in neuropsychological validity testing also indicate an average number of eight PVTs in forensic neuropsychological evaluations ( Schroeder, Martin, & Odland, 2016 ).…”
Section: Invalid Presentation On Examination (Criterion B)mentioning
confidence: 99%
“…The usefulness of PVTs and SVTs has been demonstrated in numerous studies, in particular in patients in which external incentives are present (Bianchini, Curtis, & Greve, 2006;Boone, 2013: Chapter 2), but also in psychological assessments of clinically referred patients (Dandachi-FitzGerald, van Twillert, van de Sande, van Os, & Ponds, 2016;Locke, Smigielski, Powell, & Stevens, 2008). Because of these findings, assessment validity has now become an integral part of a neuropsychological evaluation (Hirst et al, 2017).…”
Section: Introductionmentioning
confidence: 99%